Nanoencapsulation of Bacteriophages in Liposomes Prepared Using Microfluidic Hydrodynamic Flow Focusing - Cinquerrui, Salvatore; Mancuso, Francesco; Vladisavljević, Goran T.; Bakker, Saskia E.; Malik, Danish J. (Frontiers in Microbiology, 2018)
Increasing antibiotic resistance in pathogenic microorganisms has led to renewed interest in bacteriophage therapy in both humans and animals. A ‘Trojan Horse’ approach utilising liposome encapsulated phages may facilitate access to phagocytic cells infected with intracellular pathogens residing therein, e.g. to treat infections caused by Mycobacterium tuberculosis, Listeria, Salmonella and Staphyloccocus. Additionally, liposome encapsulated phages may adhere to and diffuse within mucosa harbouring resistant bacteria which are challenges in treating respiratory and gastrointestinal infections. Orally delivered phages tend to have short residence times in the gastrointestinal tract due to clinical symptoms such as diarrhoea; this may be addressed through mucoadhesion of liposomes. In the present study we have evaluated the use of a microfluidic based technique for the encapsulation of bacteriophages in liposomes having mean sizes between 100–300 nm. Encapsulation of two model phages was undertaken, an Escherichia coli T3 podovirus (size ~65 nm) and a myovirus Staphylococcus aureus phage K (capsid head ~80 nm and phage tail length ~200 nm). The yield of encapsulated T3 phages was 109 PFU/ml and for phage K was much lower at 105 PFU/ml. The encapsulation yield for E. coli T3 phages was affected by aggregation of T3 phages. S. aureus phage K was found to interact with the liposome lipid bilayer resulting in large numbers of phages bound to the outside of the formed liposomes instead of being trapped inside them. We were able to inactivate the liposome bound S. aureus K phages whilst retaining the activity of the encapsulated phages in order to estimate the yield of microfluidic encapsulation of large tailed phages. Previous published studies on phage encapsulation in liposomes may have overestimated the yield of encapsulated tailed phages. This overestimation may affect the efficacy of phage dose delivered at the site of infection. Externally bound phages would be inactivated in the stomach acid resulting in low doses of phages delivered at the site of infection further downstream in the gastrointestinal tract.